2019
DOI: 10.1590/s1984-29612019060
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal and larvicidal potential of Rosmarinus officinalis to control gastrointestinal nematodes of sheep

Abstract: Gastrointestinal Nematode Infection (GIN) are the main constraint to the production of small ruminants. Studies of medicinal plants have been an important alternative in the effort to control these parasites. Therefore, the purpose of this study was to evaluate the in vitro ovicidal and larvicidal activity of essential oil of Rosmarinus officinalis. The oil was extracted, analyzed by gas chromatography and tested on GIN eggs and larvae in six concentrations, 227.5mg/mL, 113.7mg/mL, 56.8mg/mL, 28.4mg/mL, 14.2mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
(34 reference statements)
0
11
0
1
Order By: Relevance
“…A predominância de artigos que abordam as atividade anti-helmíntica de uma ou mais plantas deve-se ao fato de que muitas são as pesquisas com produtos naturais voltados à área da produção animal. Pode-se perceber nesse estudo que nos últimos vinte anos, as pesquisas com plantas medicinais vêm crescendo entre as linhas que buscam alternativas para o controle de parasitoses em animais de produção, e os resultados dessas pesquisas têm sido bastante promissores (Sinott et al, 2012;Maciel et al, 2019;Pinto et al, 2019).…”
Section: Discussionunclassified
“…A predominância de artigos que abordam as atividade anti-helmíntica de uma ou mais plantas deve-se ao fato de que muitas são as pesquisas com produtos naturais voltados à área da produção animal. Pode-se perceber nesse estudo que nos últimos vinte anos, as pesquisas com plantas medicinais vêm crescendo entre as linhas que buscam alternativas para o controle de parasitoses em animais de produção, e os resultados dessas pesquisas têm sido bastante promissores (Sinott et al, 2012;Maciel et al, 2019;Pinto et al, 2019).…”
Section: Discussionunclassified
“…As a result of GC-MS analysis, 1,8-Cineole (Eucalyptol), the oxygenated monoterpenes that we detected with the highest rate, were also detected at high rates in the essential oils of Artemisia lancea (34.56%), Piper aduncum (55.8%), and Rosmarinus officinalis (42.11%). It was observed that essential oils of these species show high ovicidal and larvicidal activity on H. contortus [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…These drugs were proven effective in the control of GINs in previous decades and make up to 53% of total used veterinary drugs [8,10]. However, excessive use, often resulting in overfrequent treatments, has led to the development of anthelmintic resistance (AR), which has been reported in many parts of the world for different nematode species [4,11]. Consequently, the declined efficacy of most commonly used anthelmintic drug classes such as benzimidazoles (BZ) and macrocyclic lactones (ML) has caused additional high economic losses, which overall endanger modern livestock [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the declined efficacy of most commonly used anthelmintic drug classes such as benzimidazoles (BZ) and macrocyclic lactones (ML) has caused additional high economic losses, which overall endanger modern livestock [4,12]. This justifies the urgent need for new, alternative strategies such as genetic control methods, pasture management, nutritional manipulation, biological regulation (such as the use of nematophagus fungi), vaccine development and the use of different herbal-based products [11,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation